Consulting with young people: informing guidelines for children's palliative care. Issue 7 (18th November 2020) - Taylor, Johanna; Murphy, Sarah; Chambers, Lizzie; Aldridge, Jan
Abstract : Objective: Increasingly the views of young people are sought when improving healthcare; however, it is unclear how they shape policy or practice. This paper presents a consultation with young people commissioned by the National Institute for Health and Care Excellence (NICE) to inform clinical guidelines for paediatric palliative care (end-of-life care for infants, children and young people). Methods: The consultation involved qualitative thematic analysis of data from 14 young people (aged 12–18 years) with a life-limiting or life-threatening condition who took part in focus groups or interviews. The topics explored were predefined by NICE: information and communication; care planning; place of care; and psychological care. Data collection consisted of discussion points and activities using visual cues and was informed by a pilot consultation group with five young adults (aged 19–24 years). Findings were shared with participants, and feedback helped to interpret the findings. Results: Four overarching themes were identified, cutting across the predetermined topic areas: being treated as individuals with individual needs and preferences; quality of care more important than place; emotional well-being; and living as a young person. Importantly, care planning was viewed as a tool to support living well and facilitate good care, and the young people were concerned less about where care happens but who provides this. Conclusion: Young people's priorities differ from those of parents and other involved adults. Incorporating their priorities within policy and practice can help to ensure their needs and preferences are met and relevant research topics identified.